Report from the Committee on banking on the "Bill to re-charter the Bank of the Cape Fear." - Wilder, G. H. (Gaston Hillary), 1814-1873 (Document (North Carolina. General Assembly) ;, 1854)
1854 Report of the North Carolina Senate Committee on Banking on the bill to recharter the Bank of Cape Fear. The committee recommended passage with four changes to the original bill, which is not included in this document.